Clarithromycin, ixazomib, pomalidomide, dexamethasone for relapsed/refractory myeloma: survival and correlative analysis - Aaron S. Rosenberg; Emanual Maverakis; Caitlin Costello; Elizabeth A. Brem; Matthew Joseph Wieduwilt; Guillaume Luxardi; Paul Kaesberg; Keon Abedi; Samantha Herbert; Joseph Tuscano (Blood Neoplasia)
Abstract: Clarithromycin is a macrolide antibiotic with anti–multiple myeloma (MM) activity when combined with dexamethasone and immunomodulatory agents. This phase 1/2 study of clarithromycin, ixazomib, pomalidomide, and dexamethasone (ClIPd) assessed tolerability and efficacy in relapsed/refractory MM. The primary end points were the maximal tolerated and recommended phase 2 dose. Key secondary end points were the overall response rate (ORR) (≥partial response), disease control rate (DCR) (≥stable disease), progression-free survival (PFS), and overall survival (OS). All 4 medications were given at full dose for 6 cycles. Pomalidomide, ixazomib, and dexamethasone were given at reduced doses with full-dose clarithromycin in subsequent maintenance cycles until unacceptable toxicity or progression. Clarithromycin was withheld during weeks 1 to 2 of cycle 1 to facilitate correlative studies. A total of 28 patients were evaluable for response/survival. The ORR was 75%; DCR was 100%; 56% achieved ≥very good partial response (VGPR), whereas 14% achieved complete response (CR)/stringent CR. High-risk cytogenetics were not associated with ORR (Fisher exact test, P = 1) or ≥VGPR rates (Fisher exact test, P = .42). The median PFS was 22.2 months (95% confidence interval [CI], 13.3 to not reached [NR]). There was no difference in the median PFS between patients with del(17p) (26.8 months; 95% CI, 10.2 to NR) and those without (22.2 months; 95% CI, 13.3 to NR; log rank, P = .4). The median OS was NR. ClIPd combines convenient oral administration, a tolerable side effect profile, and long duration of disease control. This trial was registered at www.clinicaltrials.gov as #NCT02542657